The participation process of PEAK program for collegiate Taekwondo athletes: A grounded theory approach - Taehee Lim; Oh-Jung Kwon; Mi-Seon Yun; Junsu Bae; Yun-Kyung Yang (Korea Institute of Sport Science, 2021)
Purpose The purpose of this study was to explore the process of participation in the PEAK program of collegiate athletes based on grounded theory. Methods In-depth interviews were conducted with 12 athletes from Y University who were registered in Korea Taekwondo Association. The collected data were analyzed by using the open coding, axis coding, and selective coding of the grounded theory, completed the paradigm model among the extracted concepts, and extracted the core categories through the story outline. Results As the result of data analysis, 'participating in the PEAK program' was found as the central phenomenon, and the causal situation was 'bad attitude in class' and 'helpless daily life'. The contextual conditions were 'recognition of the need for class participation and dual career' and 'motivation to participate in the program', and the intervening conditions were 'factors that hinder participation in the program' and 'factors that help program participation'. The action/interaction strategies were 'caring climate' and 'promoting transfer', and depending on the consequence, 'learning attitude change' and 'life skill change' appeared. Conclusion Participants improved their learning attitude through the PEAK program and confirmed the possibility of life skills transfer. It is hoped that this study can lead to implementation of various studies and discussions about life skills and transfer.